Systematic analysis of the dominant types of entomophages in fruit orchards - M.Q.Parpiyeva; Sulaymonov, B.A.; Isashova, U.A.; Rakhmanova, M.K.; Rasulov, U.Sh. (Universitas Muhammadiyah Sidoarjo, 2019)
This article is focused on a systematic analysis of leaf-mining fly types that belongs to Agromyzidae family. Due to it, 2 types of leaf-mining flies were identified in agricultural plants and 1 type in weeds. Also, it was identified that Liriomyza sativae Blanchard type of leaf-mining flies that belong to 4 families are met in 12 different plants in conditions of the Andijan region. Besides that, a number of insecticides as indoxamecty, protect were used against these kinds of pests.